2006
DOI: 10.1093/ndt/gfl336
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of Toll-like receptors in lupus-like immune complex glomerulonephritis of MRL-Fas(lpr) mice

Abstract: Thus, cell-type-specific expression and regulation of TLRs may be involved in infection-associated exacerbation of immune complex glomerulonephritis of MRLlpr/lpr mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 40 publications
1
110
1
1
Order By: Relevance
“…In this process, IFN-␤ induces innate viral RNA recognition receptors in primary mesangial cells just like Tnf/IFN-␥ previously shown for cell lines of murine and human mesangial cells. 14,29 The pathogenic relevance of this mechanism for glomerulonephritis was recently demonstrated by Jørgensen et al 30 autoimmune B6.Nba2 mice and (B6Nba2 ϫ NZW)F 1 mice deficient for the type I IFNR failed to develop glomerulonephritis, although the mice had substantial glomerular immune complex deposits. 29 In summary, poly I:C RNA stimulates glomerular mesangial cells to produce large amounts of type I IFN, especially when being delivered into the intracellular cytosol where it can interact with Mda5.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this process, IFN-␤ induces innate viral RNA recognition receptors in primary mesangial cells just like Tnf/IFN-␥ previously shown for cell lines of murine and human mesangial cells. 14,29 The pathogenic relevance of this mechanism for glomerulonephritis was recently demonstrated by Jørgensen et al 30 autoimmune B6.Nba2 mice and (B6Nba2 ϫ NZW)F 1 mice deficient for the type I IFNR failed to develop glomerulonephritis, although the mice had substantial glomerular immune complex deposits. 29 In summary, poly I:C RNA stimulates glomerular mesangial cells to produce large amounts of type I IFN, especially when being delivered into the intracellular cytosol where it can interact with Mda5.…”
Section: Discussionmentioning
confidence: 90%
“…14,29 The pathogenic relevance of this mechanism for glomerulonephritis was recently demonstrated by Jørgensen et al 30 autoimmune B6.Nba2 mice and (B6Nba2 ϫ NZW)F 1 mice deficient for the type I IFNR failed to develop glomerulonephritis, although the mice had substantial glomerular immune complex deposits. 29 In summary, poly I:C RNA stimulates glomerular mesangial cells to produce large amounts of type I IFN, especially when being delivered into the intracellular cytosol where it can interact with Mda5. Type I IFN production enhances the dsRNA-induced production of proinflammatory mediators such as Il-6 as well as cell death in a positive autocrine amplification loop.…”
Section: Discussionmentioning
confidence: 90%
“…Endogenous TLR-7 ligands within deposited autoimmune complexes may also directly activate tissue-resident and recruited hematopoietic inflammatory cells in the kidney during lupus nephritis. Renal mesangial cells, however, lack TLR-7 expression and are therefore not directly activated by endogenous TLR-7 ligands (28).…”
Section: Discussionmentioning
confidence: 99%
“…The activation results in the release of adhesion molecules, cytokines and chemokines, which play a pivotal role in the innate and adaptive immune responses (Coppo et al, 2010). Interestingly, recent studies revealed the expressions of TLRs in resident renal cells, suggesting the involvement of the TLR signaling pathway in the pathogenesis of glomerular diseases (Patole et al, 2006). …”
Section: A Potential New Therapeutic Strategy For Pediatric-onset Lupmentioning
confidence: 99%
“…In order to examine the involvement of RIG-I in lupus nephritis, we conducted experimental studies using human mesangial cells. Because Th1-derived cytokines are known to be key mediators in the progression of lupus-associated renal injury, and IFN-is one of the major Th1 type cytokines with potent proinflammatory effects that exerts its effects through the upregulation of IFNinducible genes (Patole et al, 2006), we examined the effects of IFN-on the expression of RIG-I in human mesangial cells. As a result, IFN-treatment resulted in a concentration-dependent upregulation of the expression of RIG-I mRNA and protein in human mesangial cells.…”
Section: The Retinoic Acid-inducible Gene-i (Rig-i) and Lupus Nephritismentioning
confidence: 99%